Short Communication: Biological aspects of Charybdis anisodon (De Haan, 1850) in Lasongko Bay, Central Buton, Southeast Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2018)
Hamid A, Wardiatno Y. 2018. Short Communication: Biological aspects of Charybdis anisodon (De Haan, 1850) in Lasongko Bay, Central Buton, Southeast Sulawesi, Indonesia. Biodiversitas 19: 1755-1762. Data on the biological aspects of Charybdis anisodon (De Haan, 1850) were still very limited. This study was aimed to determine the distribution of size, growth type, sex ratio and spawning season of C. anisodon in Lasongko Bay, Central Buton, Southeast Sulawesi. Crab collection was conducted from May 2013 to March 2014 using a crab gillnet. The carapace width of males and females C. anisodon ranged between 3.05-7.61 cm and 3.45-7.98 cm, respectively. Mann-Whitney test showed that width and length of carapace of males and females were significantly different (p
Keywords: Allometric relationship; crustacea; growth type; sex ratio; spawning season; two-spined arm swimming crab